Finite Element Analysis of Impact Test for Fiber Metal Laminate Fuselage Using SolidWorks ® Simulation - Awang Kechik, Afiqah (2020)
Fuselage is the central body of an airplane that is designed to accommodate the crew and passengers. In a simple word, fuselage is a body which is mean the external structure of vehicle. Different types of aircraft have different types of fuselages, depending on how quickly they are required to travel and what they are carrying, but a fuselage is always hollow and always has a front cockpit. The main objective is to design a new fuselage with a new material that have the specific strength that may help to enhance the properties of fuselage. The fuselage model is created using the Finite Element Analysis via SolidWorks® software. The dynamic analysis is made to the test the maximum stress and maximum displacement of material. The materials used for the test are aluminium alloy Al 2042-T3, titanium alloy Ti-6Al-4V (SS) and GLARE. The three type of material were compared between each other by impact test. The results are shown in terms of stress and terms of displacement. It has been found that GLARE is the best material in terms of displacement while in terms of stress, aluminium alloy is the best material in this study.